Climate Change Governance and Ecosystem Sustainability in Sub-Saharan Africa - Dan-Woniowei, Fie David; IKPORUKPO, Iyabrade; Kalagbo, Samuel B. (Advances in Social Sciences Research Journal, 2022)
This study assesses whether climate change governance has improved ecosystem sustainability in Sub-Sahara Africa (SSA) from 2012 to 2021. It relied on the African Strategy on Climate Change (ASCC), May 2014 for the assessment and adopted the ecosystem approach (EA) for analysis. The study discovered that the ASCC May 2014 was quite elaborate, yet does not explicitly, address the issues bothering ecosystem sustainability (ES). Rather, efforts and considerations were organized around climate change mitigation financing and development, which motive was to perpetuate the exploitation of the continent’s natural resources. It also discovered that many of the policies and frameworks intended to mitigate climate change and adaptation have not been adequately implemented due to bad governance. The study, therefore, recommends that future African strategic policies and frameworks on the environment cum engagements with climate change governance actors such as development partners, regulators, and other stakeholders either on the global, regional, or national levels should be properly directed to enhance ecosystem sustainability. In addition, such outcomes should be implemented adequately to safeguard the livelihoods of the millions of indigenous people in the SSA.